Movement detection properties and structure of stationary receptive fields of single neurons in the cat extrastriate area 21a - Aslanian, H.R.; Khachvankian, D.K.; Harutiunian-Kozak, B.A.; Tokhmakhyan, G.G.; Khachatrian, T.S.; Kozak, J.A. (Нейрофизиология, 2014)
Response patterns of single neurons in the extrastriate area 21a of the cat cortex to moving
visual stimuli were studied, along with juxtaposition to the structure of their stationary
receptive field. First, the precise mapping of stationary RFs was performed by flashing bright
spots; then, moving visual stimuli of different shapes and sizes with two opposite contrasts
were presented. We found that the majority of investigated neurons with a homogenous
stationary RF organization demonstrate significant differences in their activity profiles
depending on the size, shape, and contrast of the applied moving visual stimulus. The data
obtained support a model in which the RF stationary structure undergoes specific dynamic
changes due to simultaneous activation of the RF surround by the moving visual image; this
provides more accurate incorporation of moving image information in movement detection. Досліджували патерни відповідей поодиноких нейронів
екстрастріатного поля 21a кори великих півкуль кота на
пред’явлення рухливих візуальних стимулів, одночасно беручи до уваги структуру стаціонарних рецептивних полів
(РП) цих нейронів. Спочатку виконували прецизійне картування стаціонарних РП за допомогою пред’явлення яскравих плям, що спалахували; після цього пред’являли рухливі
візуальні стимули різних форм та розмірів з двома протилежними контрастами. Значна більшість досліджених нейронів із гомогенною організацією стаціонарних РП демонстрували істотно відмінні профілі активності, залежні від
величини, форми та контрасту рухливих зорових стимулів,
що пред’являлися. Отримані дані узгоджуються з моделлю,
в рамках якої стаціонарна структура РП піддається специфічним динамічним модифікаціям завдяки одночасній активації оточення РП під дією рухливого візуального образу. Це
забезпечує точніше залучення інформації щодо руху зображення до процесу детекції такого руху.